USE OF My-BCA FACILITIES IN ATTRACTING CUSTOMER INTEREST IN PT. CENTRAL BANK ASIA (BCA) (Empirical Study of BCA KCU MALANG Office) - Putri Pamungkas, Restu (International Journal of Business, Law, and Education, 2023)
Competition in the banking world currently encourages every banking agency to provide the best service according to its customers' needs. One effort to improve service to customers is by utilizing developments in information technology. Utilization of this technological development will have an impact on the influx of new customers, including at BCA bank. BCA Bank is always quick to respond to technological developments and always wants to provide excellent service to its customers, so they always upgrade their facilities, including providing a new application, namely my-BCA. This research is aimed at uncovering the use of My-BCA facilities in attracting customer interest, so a qualitative approach is more suitable for use in this study. Research data was collected through participant observation and interviews with informants. Based on the results of the descriptive analysis used in this research, three findings were obtained related to customer knowledge about the My-BCA application; The impact of the new application (My-BCA) during the Covid-19 pandemic; and the benefits of My-BCA for customers. In terms of knowledge, there are still many customers who don't know about the My BCA application. However, even though many people don't know the My-BCA application, the millennial generation is more responsive because they adapt more quickly to technological developments, so they use this application more. In terms of impact and benefits, the My-BCA application is a more effective and efficient application, because one application can be used for more than one account number and customers can use it to carry out banking transactions from anywhere, making it more practical